Negotiating reality as an approach to intercultural competence - Ariane Berthoin Antal; Victor Friedman (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2003)
In an increasingly global business environment, managers must interact effectively with people who have different values, behavioral norms, and ways of perceiving reality. Many jobs now entail an international dimension, so the need to develop intercultural competences has taken on a greater importance for more people in business than ever before. Intercultural competence is the ability to recognize and use cultural differences as a resource for learning and for generating effective responses in specific contexts. We conceive of this as negotiating reality. The approach draws on concepts from international management, sociology, crosscultural psychology, action science and conflict resolution. – – In einer zunehmend globalisierten Umwelt müssen Führungskräfte immer häufiger mit Menschen aus anderen Kulturen zusammenzuarbeiten, die unterschiedliche Wertevorstellungen haben, verschiedene Verhaltensnormen pflegen und ihre jeweils eigene Wahrnehmung der Realität haben. Damit steigt der Bedarf an interkultureller Kompetenz, der Fähigkeit, kulturelle Unterschiede als Lernressourcen zu erkennen und für die jeweilige Situation adäquate Lösungen zu erarbeiten und einzusetzen. Dieser Beitrag beschreibt einen innovativen Ansatz, den wir negotiating reality nennen, der sich aus unterschiedlichen Theoriebereichen, u.a. dem internationalen Management, der Soziologie, der interkulturellen Psychologie, und der Konfliktforschung speist.
Keywords: 300; Multikulturell; Kompetenz; Interkulturelles Management